2006
DOI: 10.2136/sssaj2005.0350
|View full text |Cite
|
Sign up to set email alerts
|

No‐Till Corn/Soybean Systems Including Winter Cover Crops

Abstract: The use of winter cover crops (WCC) such as hairy vetch (Vicia villosa Roth) and cereal rye (Secale cereale L.), in a corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] rotation provides long‐term benefits that are generally overlooked. There is a particular lack of information regarding the effects of WCC on soil physical and chemical properties. The objective of this study was to assess the effects of four crop sequences (C/S, corn‐fallow/soybean‐fallow; C‐R/S‐R, corn‐rye/soybean‐rye; C‐R/S‐V, corn‐rye/soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
190
8
37

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(254 citation statements)
references
References 48 publications
19
190
8
37
Order By: Relevance
“…This is understandable, since most rye roots were concentrated in the 0-10 cm depth. Our results agree with those by Villamil et al (2006) who reported similar findings. The cover crop x depth of sampling interaction showed that Ds/ Do was 25% (0-10 cm) and 14% (10-20 cm) greater in plots planted to rye as compared with plots with no cover crop.…”
Section: Resultssupporting
confidence: 94%
“…This is understandable, since most rye roots were concentrated in the 0-10 cm depth. Our results agree with those by Villamil et al (2006) who reported similar findings. The cover crop x depth of sampling interaction showed that Ds/ Do was 25% (0-10 cm) and 14% (10-20 cm) greater in plots planted to rye as compared with plots with no cover crop.…”
Section: Resultssupporting
confidence: 94%
“…However, in our study higher TOC were found in the CC treatments since 2012 that are in agreement with other short term experiments (Nivelle et al, 2016;Veenstra et al, 2007). Particularly, Villamil et al (2006) and Mazzoncini et al…”
Section: Resultssupporting
confidence: 93%
“…Total organic carbon (TOC) content is a soil quality indicator that is affected by the changes in the crop management such as intensive tillage and the addition of crop residues to the soil (Chavarría et al, 2016;Muñoz et al, 2007;Nivelle et al, 2016;Veenstra et al, 2007;Villamil et al, 2006). Benefits in soil structure are related to its accumulation in the soil and an increase in the formation and stabilization of soil microaggregates and macroaggregates (Beare et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Carof et al (2007) showed that under no-tillage cover crops enhanced pore continuity in a silt loam in northern France, while Bodner et al (2008) found that cover crops stabilised effective pore properties over winter on a silt loam soil in semi-arid Eastern Austria. Villamil et al (2006) studied the effect of inclusion of rye, vetch and vetch/rye mixture as cover crops in a corn-soybean notillage rotation on a silt loam soil in Illinois, USA, with a continental summer rainfall climate. Cover crops increased organic carbon, aggregate stability and water holding capacity, while reducing bulk density and penetration resistance.…”
Section: Organic Matter Inputmentioning
confidence: 99%